Pan-cancer analysis shows that TNFSF4 is a potential prognostic and immunotherapeutic biomarker for multiple cancer types including liver cancer - Zhaoda Deng; Lincheng Li; Zihe Meng; Guineng Zeng; Rui Cao; Rong Liu (BMC Cancer)
Abstract Background As a member of the tumor necrosis factor (TNF) superfamily, tumor necrosis factor superfamily member 4 (TNFSF4) is expressed on antigen-presenting cells and activated T cells by binding to its receptor TNFRSF4. However, tumorigenicity of TNFSF4 has not been studied in pan-cancer. Therefore, comprehensive bioinformatics analysis of pan-cancer was performed to determine the mechanisms through which TNFSF4 regulates tumorigenesis. Methods RNA-seq data for 33 cancers were analyzed from UCSC XENA database. Online websites and databases were used to investigate TNFSF4’s biological function, epigenetic modifications, genetic alterations, and tumor immunity. Furthermore, cell phenotype experiment and tumor xenotransplantation experiment were performed to determine the biological functions of TNFSF4. Results The pan-cancer analysis showed that TNFSF4 was upregulated in several tumors. Significant relationships between TNFSF4 expression and single-cells data were also observed in numerous cancer types. TNFSF4 expression correlated with the expression of immune checkpoint genes and could influence various drug sensitivity. Vitro and vivo experiments showed that TNFSF4 could promote the development and progression of Hepatocellular Carcinoma (HCC). Conclusions TNFSF4 was upregulated in multiple cancer types and promoted the development and progression of cancers through several mechanisms including regulation of the tumor-infiltration of immune cells. Our study shows that TNFSF4 is a promising prognostic and immunotherapeutic biomarker in some malignant tumors. Graphical Abstract